Developing of seaweed juice Halymenia durvilae Industry as a source antioxidant in Winuri VIlage, Likupang Subdistrict, North Minahasa Regency - Sanger, Grace; Damongilala, Lena; Salindeho, Netty (Jurnal Ilmiah Platax, 2024)
The Community Service Program is located in Winuri Village, which is very geographically strategic for developing the industry of processing seaweed juice.   The village is a tourism region, so marketing food and beverage is easy. Generally, juices ready to be consumed in the market are juices from the fruit of the terrestrial plant,  whereas the juice of seaweed is very rare in the market.  This matter caused the community to be unaware of seaweed's benefits for human health, especially for preventing degenerative diseases, such as cancer.  Therefore is necessary to encourage the government or community to develop processed products of seaweed beverages, more will be developed to build an industry,  that has the main purpose of increasing public welfare. The targets of the Community Service Program are: To produce juice of seaweed that fulfills sanitation and hygienic standards; 2. To encourage the development of the seaweed juice industry.  The Implementation methods of the program that are agreed upon with the Partner are: 1. The problem of seaweed juice production, marketing, and finances; 2. The method to solving  the problems with counseling,  training, assistance, and evaluation; Keywords: Hygiene, industry, sanitation, dietary fiber Abstrak Program Pengabdian pada masyarakat (PKM) ini berlokasi di Wiuri yang  secara geografis sangat strategis untuk dikembangkan industri pengolahan minuman rumput laut. Desa  ini merupakan daerah wisata, sehingga pemasaran makanan dan minuman akan mudah. Saat ini kebanyakan minuman siap konsumsi  di pasaran  adalah minuman dari buah, tetapi minuman dari rumput laut jarang ditemui dilingkungan masyarakat. Hal ini disebabkan karena banyak masyarakat belum menyadari manfaat rumput laut untuk kesehatan. Oleh karena itu perlu usaha untuk mendorong pengembangan produk pengolahan pada masyarakat kemudian dapat ditingkatkan menjadi skala industri untuk meningkatkan kesejahteraan masyrarakat. Tujuan PKM ini yaitu 1. Memproduksi minuman rumput laut memenuhi syarat sanitasi dan higienis; 2. Mendorong pengembangkan usaha industri minuman sirup rumput laut. Adapun metode pelaksanaan yang disepakati dengan mitra yaitu: 1. Masalah produksi minuman sirup rumput laut, pemasaran produk dan keuangan; 2. Metode untuk menyelesaikan masalah dengan penyuluhan, pelatihan, pendampingan dan evaluasi; Kata kunci: Higienis, industri, sanitasi, serat.